1996
DOI: 10.1128/jb.178.7.1914-1918.1996
|View full text |Cite
|
Sign up to set email alerts
|

A recent fixation of cfiA genes in a monophyletic cluster of Bacteroides fragilis is correlated with the presence of multiple insertion elements

Abstract: Small-subunit ribosomal DNA sequences of 16 strains of Bacteroides fragilis were determined and compared with previously published sequences. Three phylogenetic methods (the neighbor-joining, maximum-likelihood, and maximum-parsimony methods) as well as a bootstrap analysis were used to assess the robustness of each topology. All phylogenetic analyses demonstrated that the B. fragilis strains were clearly divided into two robust monophyletic units which corresponded to the cfiA-negative and cfiA-positive group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…The second group was characterized by the absence of the cfiA gene and of the associated insertion sequences, the frequent presence of the cepA gene, and a higher genetic heterogeneity (Podglajen et al, 1995 ;Ruimy et al, 1996). By including strains obtained from Johnson (1978) in their 16S rRNA sequence comparison, Ruimy et al (1996) showed that the two groups described above could be related to the DNA homology groups II and I, respectively. Despite these findings, there is as yet no information dealing with the genetic relationship between invasive and noninvasive strains, human and animal strains and strains of different geographical origin.…”
Section: Abbreviationsmentioning
confidence: 96%
See 2 more Smart Citations
“…The second group was characterized by the absence of the cfiA gene and of the associated insertion sequences, the frequent presence of the cepA gene, and a higher genetic heterogeneity (Podglajen et al, 1995 ;Ruimy et al, 1996). By including strains obtained from Johnson (1978) in their 16S rRNA sequence comparison, Ruimy et al (1996) showed that the two groups described above could be related to the DNA homology groups II and I, respectively. Despite these findings, there is as yet no information dealing with the genetic relationship between invasive and noninvasive strains, human and animal strains and strains of different geographical origin.…”
Section: Abbreviationsmentioning
confidence: 96%
“…Three specific insertion sequence elements, IS1186, IS942 and IS4351, providing the promoter region for the cfiA gene, were shown to be confined to this group (Podglajen et al, 1995). The second group was characterized by the absence of the cfiA gene and of the associated insertion sequences, the frequent presence of the cepA gene, and a higher genetic heterogeneity (Podglajen et al, 1995 ;Ruimy et al, 1996). By including strains obtained from Johnson (1978) in their 16S rRNA sequence comparison, Ruimy et al (1996) showed that the two groups described above could be related to the DNA homology groups II and I, respectively.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). Ruimy et al [4], using a 729-bp internal fragment of the c®A sequence as a probe, demonstrated two types of c®A genes. One type was characterised by a strong hybridisation signal and the other reacted only weakly; this hybridisation difference might have been due to the existence of the two alleles found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, some strains produce an enterotoxin [1,2]. Studies with multilocus enzyme electrophoresis (MLEE) [3] and other molecular techniques ± particularly 16S rRNA sequencing [4] and DNA±DNA hybridisation [5] ± have shown the separation of the population into two groups presenting an extensive genetic distance one from the other (divisions I and II). Division I was characterised by the frequent presence of the cepA gene (encoding a serine-â-lactamase of Ambler's class A) and the absence of the c®A gene (encoding a metallo-â-lactamase of Ambler's class B).…”
Section: Introductionmentioning
confidence: 99%